Kalimat Imperatif pada Pidato Nadiem Makarim Rekomendasi sebagai Bahan Ajar Teks Pidato Persuasif SMP - Laila Atiyyah Ramadhani Sitorus; Usiono Usiono (PT. Alahyan Publisher Sukabumi, 2025)
This research was conducted to describe the use of imperative sentences in Mr. Nadiem Makarim's speech on the Ministry of Education and Culture channel and provide recommendations as teaching materials for language texts.and Culture and provide recommendations as teaching materials for persuasive language texts in secondary schools. The approach used is descriptive qualitative with technology analysis component (BLU). The command statements used include: (1) Smooth command sentences contain several sentence markers: try, please, please. (2) Imperative requests are made with the word please. (3) In imperative invitation sentences, the word markers “come on” and “come on” are used. (4) Imperative sentences are marked with the word “not”.Use subtle imperatives, imperatives of request, imperatives of invitation, imperatives of prohibition, and imperatives of suggestion as well as imperatives that give permission to add imperatives as materials for intermediate level (junior high) persuasive language texts. recommended. Congratulations on the proposal. The conclusion of this study is that Nadiem Makarim's speech contains as many as four command sentences that can be used as material for persuasive speech text recommendations and can be added to the order of permission, command sentences as suggestions, and imperative sentences as. Congratulations in Nadiem Makarim's speech cannot be found.